Adjacency Pairs In Avatar Movie - Padma Negara, I Putu Agus; Sedeng, I Nyoman (Udayana Journal of Social Sciences and Humanities; Vol 8 No 1 (2024): Vol 8 No 1 (2024): UJoSSH, Februari 2024, 2024)
This study entitled “Adjacency Pairs in Avatar Movie” is a study about adjacency pairs and generally about conversation analysis. This study investigates the types of adjacency pairs, and the preferred and dis-preferred responses of adjacency pairs which are used between characters in Avatar movie. Avatar movie was the data source of this study, and the data was collected by using the library research and documentation method. This study used qualitative descriptive method to analyze the data of the problems. The theory that is used in this study is the theory of conversational analysis specifically in adjacency pairs by Levinson (1983) in the book “Pragmatics”. For the results, there are a total of 16 types of adjacency pairs in conversation used between characters in Avatar movie. In total, there are 97 data of conversation of adjacency pairs found in the movie. Based on the types of adjacency pairs found in this study, there are 9 types of adjacency pairs determined as preferred responses and there are a total of 73 data of adjacency pairs as the format of preferred responses. In dis-preferred responses, there are 7 types of adjacency pairs and 24 data found in the movie of this study. The most types of adjacency pairs found in the movie are the types of question-answer (29 data), telling-acceptance (20 data), telling-refusal (10 data), and request-acceptance (8 data). Keywords: Adjacency Pairs, Conversation Analysis, Conversation